Running the Border Gauntlet : the Mexican Migrant Controversy. - French, Laurence, 1941- (ABC-CLIO, 2010)
Although immigration and the U.S./Mexico border are perennial election issues, few Americans are aware of the long history of racial, political, religious, and class conflict that have resulted in America's contentious immigration policies. Running the Border Gauntlet traces this complex history, examining events that eventually led to the forceful annexation of the majority of Mexico under the pretense of Manifest Destiny and that contribute to tensions between the two nations today. The story begins with religious discord between Protestants and Catholics and continues through the developme.